Drama kot oblika (iz) "predmiselnega kaosa" - Lukan, Blaž (Jezik in slovstvo, 2015)
The article is an analysis of Vitomil Zupan's last play Notes on the System (Zapiski o sistemu, 1975) from 1975. The play has barely received mention in the Slovenian literary-historical context, and the few references to it are marked by entirely arbitrary judgements about its supposed critical view of the "socialist system" of the time. A more notable response was elicited by the play's production in the Glej Experimental Theatre in 1979, when theatre critics on the whole praised the achievements of the director, while finding fault with some of the formal features of the play. The present article engages with these "faults", which are instead understood as new, transcendent qualities of the text, with which the author surpasses the set boundaries of Slovenian theatre production of the time, and, in a way, also surpasses "himself". The line of thinking follows two directions: the first is "formal" and shows the Notes on the System to possess dramaturgical or formal elements that would much later be instituted by postdramatic (or theatre) practice, while the second relates to the content, finding ideological configurations in the text that go far beyond simplistic truisms.
Keywords: Zupan, Vitomil, 1914-1987; "Zapiski o sistemu"; Slovene literature; slovenska književnost; slovenska dramatika; slovenski dramatiki; metadrama; postdramskost